Encontros de diálogos no pré-natal e o cuidado materno às intercorrências com o recém-nascido - Lino, Amanda de Assunção (2016)
Introduction: The promotion of child development is among the priorities of the Health Agenda The prenatal period is considered as strategic for bond formation and empowerment of women, and we can also tell your family. Direct the focus to the child, the enhancement and empowerment of caregivers and family are essential for building knowledge and thus promote child development. This study is linked to the development of Dialogue Meetings (DM) among pregnant women and researchers during the prenatal period, with a view to empowering women and families to face common during the neonatal period. Objective: This study aims to analyze the influence of ED in prenatally in maternal care experience to term newborn, with special attention to health complications in the first month after the child's birth. Methodology: This is an exploratory qualitative study, adopting as a theoretical Symbolic Interactionism and the methodological framework to Bardin Content Analysis. The results are derived from interviews with seven women. There is approval of the study with an ethics committee under number 957814. Results: Results are presented from two themes: "Breastfeeding and infant colic" and "care for the newborn and maternity." The women report difficulties in breastfeeding, especially in terms of grip and handling. In addition, experience the infant colic and limitations of resolution, the need to take care of the umbilical stump, skin manifestations and flow / milk regurgitamentos. All in a context immersed knowledge and popular beliefs. Experience insecurities and fears, but are lived in the DM support for facing them. Conclusion: The results indicate contributions of DM in the management of health complications in children in their first month of life. This determines your statement as a strategy for pre-natal practices in primary health care.